Contribution of hepatic and extrahepatic insulin resistance to the pathogenesis of impaired fasting glucose role of increased rates of gluconeogenesis - BOCK, Gerlies; CHITTILAPILLY, Elizabeth; BASU, Rita; TOFFOLO, Gianna; COBELLI, Claudio; CHANDRAMOULI, Visvanathan; LANDAU, Bernard R; RIZZA, Robert A (Diabetes (New York, N.Y.), 2007)
To determine the contribution of hepatic insulin resistance to the pathogenesis of impaired fasting glucose (IFG). Endogenous glucose production (EGP) and glucose disposal were measured in 31 subjects with IFG and 28 subjects with normal fasting glucose (NFG) after an overnight fast and during a clamp when endogenous secretion was inhibited with somatostatin and insulin infused at rates that approximated portal insulin concentrations present in IFG subjects after an overnight fast (approximately 80 pmol/l, "preprandial") or within 30 min of eating (approximately 300 pmol/l, "prandial"). Despite higher (P < 0.001) insulin and C-peptide concentrations and visceral fat (P < 0.05), fasting EGP and glucose disposal did not differ between IFG and NFG subjects, implying hepatic and extrahepatic insulin resistance. This was confirmed during preprandial insulin infusion when glucose disposal was lower (P < 0.05) and EGP higher (P < 0.05) in IFG than in NFG subjects. Higher EGP was due to increased (P < 0.05) rates of gluconeogenesis in IFG. EGP was comparably suppressed in IFG and NFG groups during prandial insulin infusion, indicating that hepatic insulin resistance was mild. Glucose disposal remained lower (P < 0.01) in IFG than in NFG subjects. Hepatic and extrahepatic insulin resistance contribute to fasting hyperglycemia in IFG with the former being due at least in part to impaired insulin-induced suppression of gluconeogenesis. However, since hepatic insulin resistance is mild and near-maximal suppression of EGP occurs at portal insulin concentrations typically present in IFG subjects within 30 min of eating, extrahepatic (but not hepatic) insulin resistance coupled with accompanying defects in insulin secretion is the primary cause of postprandial hyperglycemia.